Quantifying and Mitigating Wind‐Induced Undercatch in Rainfall Measurements. Issue 6 (7th June 2018) - Pollock, M. D.; O'Donnell, G.; Quinn, P.; Dutton, M.; Black, A.; Wilkinson, M. E.; Colli, M.; Stagnaro, M.; Lanza, L. G.; Lewis, E.; Kilsby, C. G.; O'Connell, P. E.
Abstract: Despite the apparent simplicity, it is notoriously difficult to measure rainfall accurately because of the challenging environment within which it is measured. Systematic bias caused by wind is inherent in rainfall measurement and introduces an inconvenient unknown into hydrological science that is generally ignored. This paper examines the role of rain gauge shape and mounting height on catch efficiency (CE), where CE is defined as the ratio between nonreference and reference rainfall measurements. Using a pit gauge as a reference, we have demonstrated that rainfall measurements from an exposed upland site, recorded by an adjacent conventional cylinder rain gauge mounted at 0.5 m, were underestimated by more than 23% on average. At an exposed lowland site, with lower wind speeds on average, the equivalent mean undercatch was 9.4% for an equivalent gauge pairing. An improved‐aerodynamic gauge shape enhanced CE when compared to a conventional cylinder gauge shape. For an improved‐aerodynamic gauge mounted at 0.5 m above the ground, the mean undercatch was 11.2% at the upland site and 3.4% at the lowland site. The mounting height of a rain gauge above the ground also affected CE due to the vertical wind gradient near to the ground. Identical rain gauges mounted at 0.5 and 1.5 m were compared at an upland site, resulting in a mean undercatch of 11.2% and 17.5%, respectively. By selecting three large rainfall events and splitting them into shorter‐duration intervals, a relationship explaining 81% of the variance was established between CE and wind speed. Plain Language Summary: This study was motivated by how challenging it is to measure rainfall accurately, despite it appearing to be very simple. Rainfall measurement is important to society because it has so many everyday uses, such as food production and weather forecasting, and applications that are critical to life, such as flood warning and effective management of water resources. Rainfall is difficult to measure because it varies so much in time and space, and the measurement of rain is highly affected by how windy it is, which also varies in time and space. Therefore, when it rains at the same time as being very windy, which is common during many storms, rainfall measurements are greatly underestimated. The uplands generally receive more rainfall and higher wind speeds than the lowlands, therefore it follows that we underestimate rainfall by more in the uplands. This is important because rainfall measurements in the uplands are sparse, yet it is in such areas where many floods originate. This study shows that the underestimation of rainfall at a site in the windy Scottish uplands was more than 23% on average. It then suggests some techniques that can be implemented to improve the measurement of rainfall. Key Points: Rainfall in windy upland areas can be greatly underestimated due to wind‐induced undercatch The mounting height and shape of a rain gauge is more important for accurate rainfall measurement than is widely appreciated An improved‐aerodynamic rain gauge shape is the simplest and cheapest method of enhancing rainfall catch